Combined-Acupoint Electroacupuncture Induces Better Analgesia via Activating the Endocannabinoid System in the Spinal Cord. (15th September 2022) - Jiang, Zhenhua; Li, Yuheng; Wang, Qun; Fang, Zongping; Deng, Jiao; Zhang, Xinxin; Shen, Bowen; Wu, Zhixin; Yang, Qianzi; Xiong, Lize
Abstract : Electroacupuncture (EA) therapy has been widely reported to alleviate neuropathic pain with few side effects in both clinical practice and animal studies worldwide. However, little is known about the comparison of the therapeutic efficacy among the diverse EA schemes used for neuropathic pain. The present study is aimed at investigating the therapeutic efficacy discrepancy between the single and combined-acupoint EA and to reveal the difference of mechanisms behind them. Electroacupuncture was given at both Zusanli (ST36) and Huantiao (GB30) in the combined group or ST36 alone in the single group. Paw withdrawal mechanical threshold (PWMT) was measured to determine the pain level. Electrophysiology was performed to detect the effects of EA on synaptic transmission in the spinal dorsal horn of the vGlut2-tdTomato mice. Spinal contents of endogenous opioids, endocannabinoids, and their receptors were examined. Inhibitors of CBR (cannabinoid receptor) and opioid receptors were used to study the roles of opioid and endocannabinoid system (ECS) in EA analgesia. We found that combined-acupoint acupuncture provide stronger analgesia than the single group did, and the former inhibited the synaptic transmission at the spinal level to a greater extent than later. Besides, the high-intensity stimulation at ST36 or normal stimulation at two sham acupoints did not mimic the similar efficacy of analgesia in the combined group. Acupuncture stimulation in single and combined groups both activated the endogenous opioid system. The ECS was only activated in the combined group. Naloxone totally blocked the analgesic effect of single-acupoint EA; however, it did not attenuate that of combined-acupoint EA unless coadministered with CBR antagonists. Hence, in the CCI-induced neuropathic pain model, combined-acupoint EA at ST36 and GB30 is more effective in analgesia than the single-acupoint EA at ST36. EA stimulation at GB30 alone neither provided a superior analgesic effect to EA treatment at ST36 nor altered the content of AEA, 2-AG, CB1 receptor, or CB2 receptor compared with the CCI group. Activation of the ECS is the main contributor of the better analgesia by the combined acupoint stimulation than that induced by single acupoint stimulation.